2012
DOI: 10.1002/term.1556
|View full text |Cite
|
Sign up to set email alerts
|

Construction of tissue-engineered osteochondral composites and repair of large joint defects in rabbit

Abstract: In this study, a novel three-dimensional (3D) heterogeneous/bilayered scaffold was constructed to repair large defects in rabbit joints. The scaffold includes two distinct but integrated layers corresponding to the cartilage and bone components. The upper layer consists of gelatin, chondroitin sulphate and sodium hyaluronate (GCH), and the lower layer consists of gelatin and ceramic bovine bone (GCBB). The two form a 3D bilayered scaffold (GCH-GCBB), which mimics the natural osteochondral matrix for use as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 60 publications
0
27
0
2
Order By: Relevance
“…Fifteen studies [49, 65, 72, 75, 81, 86, 89–97] used a mixture of solutions prepared from hyaluronic acid [65, 92, 94–97], phosphate buffer solution [91], plasma [75], basal medium with chondrogenesis [89], collagen acid [93], sodium alginate [86] or a growth factor medium [90]. Two studies used MSCs only [49, 72].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies [49, 65, 72, 75, 81, 86, 89–97] used a mixture of solutions prepared from hyaluronic acid [65, 92, 94–97], phosphate buffer solution [91], plasma [75], basal medium with chondrogenesis [89], collagen acid [93], sodium alginate [86] or a growth factor medium [90]. Two studies used MSCs only [49, 72].…”
Section: Resultsmentioning
confidence: 99%
“…Cell sources and biological protein incorporation methods are discussed, addressing their interaction with scaffolds and highlighting the potential for creating a new generation of bilayered composite scaffolds that can mimic the native interfacial tissue properties, and are able to adapt to the biological environment 39 . Deng et al 45 evaluated the efficacy of a three-dimensional (3D) heterogeneous/bilayered scaffold, consists of gelatin, chondroitin sulphate and sodium hyaluronate (GCH) and ceramic bovine bone (GCBB), to repair large defects in rabbit joints. In summary, this study demonstrated that a novel scaffold, comprising a top layer of GCH, having mechanical properties comparable to native cartilage, and combined with chondrocytes and bone marrow stem cells (BMSCs) could be used to repair large osteochondral defects in joints.…”
Section: Resultsmentioning
confidence: 99%
“…high substrate stiffness and normoxic oxygen tension. The substrate stiffness was determined based on the phenotype of the cells in the surrounding lattice points 3 . The stiffness was considered high if the differentiating MSC was within the vicinity of a mature OB.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of these strategies is to use cells, scaffolds and growth factors to regenerate the damaged tissue and thus provide long term relief to the patient (2). While numerous advances have been made in the design of multiphasic scaffolds (3)(4)(5), cell culture protocols (6,7) and growth factor releasing materials (8,9), a number of issues still exist which limit the widespread implementation of these techniques. One of the most prominent of these is promoting the formation of stable bone and cartilage within the osseous and chondral regions of the defect respectively.…”
Section: Introductionmentioning
confidence: 99%